Pedagogical practice in rural contexts, and the problem of reading comprehension. (2022)
This article aims to reflect at a general level about the process of investigative pedagogical practice of deepening the Bachelor’s Degree in Basic Education with an emphasis on Mathematics, Humanities and Spanish Language, developed at the Adolfo María Jiménez educational institution in times of pandemic (according to the Ministry of National Education in resolution 385 of March 12, 2020) in a rural area of the municipality of Sotaquirá, Boyacá. Getting into the different educational, social and cultural processes and contexts that led to an education related to the new non-face-to-face school model, with the completion of learning guides in the area of Spanish language. When entering this area, reflection is made about the processes encountered and different difficulties in terms of the ability to understand a reading, with which we want to make known aspects related to the lack of reading comprehension argued by different authors, taking into account it takes into account incident factors at the educational level in each of the social contexts of the students that is taken into account; attending to the curriculum according to (law 115 of 1194) raises the pedagogical incidence that allows us to address from the real the deficiency that exists in the reading process and the lack of bases that promote the taste for reading in the different disciplines where the shortcomings. This document takes collection from the experience and observation of personal atypical practice described by the author.